Mental Health Effects of COVID-19 in Socially Vulnerable Children - Adela Bertella, María (2022)
The aim of the present mixed (qualitative; quantitative) study was to explore the effects of the COVID-19 pandemic in the mental health of a group of children between 7 and 11 years old during 2021. We utilized a survey elaborated ad-hoc and a graphic technique in which children had to make two drawings: how they felt during the pandemic and how they remembered they felt before the pandemic. Overall, 72 caretakers (67 women, 5 men) and 72 children (43 girls, 29 boys) participated in the study. All of them attended a primary health center in Buenos Aires Province. The families belong to a socially vulnerable community. While exploring the children´s personal area (as identified by the caretakers), a significant difference was obtained between prevalent symptoms related to fears, worries, difficulties in feeding, sleeping and somatizations during the pandemic and those presented before COVID-19. The analysis of both the drawings and children’s verbalizations also highlight the experiences of fears, worries and sadness felt by the children during the pandemic. Question remains as to whether these difficulties observed ext of the pandemic are on their way to being solved or whether these consequences will persist.